2018
DOI: 10.15570/actaapa.2018.5
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous squamous cell carcinoma complicating hidradenitis suppurativa: a review of the prevalence, pathogenesis, and treatment of this dreaded complication

Abstract: Prevalence of squamous cell carcinoma in patients with chronic hidradenitis suppurativa A review of the articles found 85 cases of SCC arising from HS reported in the English literature to date (6-13). A 2016 report by Jourabchi et al. (6) described 80 of these cases, and we found five additional cases published since that time (Table 2). Among these five new cases, the mean history of HS prior to SCC diagnosis was 26 years. The mean age at diagnosis was 52 years. SCC developed from longstanding HS of predomin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
69
1
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(82 citation statements)
references
References 26 publications
4
69
1
8
Order By: Relevance
“…2,3 It develops three times more often in males, probably due to the more frequent gluteal and perineal localization in males and is highly associated with smoking. [1][2][3][4] The average period between HS onset and SCC developing is estimated of 27 ± 9.9 years, 1,4 significantly longer than in the presented case (~2.5 years). In addition, cases in medical literature report SCC developing in advanced HS, whereas in the presented case the condition is assessed as hurley I-II.…”
mentioning
confidence: 45%
See 2 more Smart Citations
“…2,3 It develops three times more often in males, probably due to the more frequent gluteal and perineal localization in males and is highly associated with smoking. [1][2][3][4] The average period between HS onset and SCC developing is estimated of 27 ± 9.9 years, 1,4 significantly longer than in the presented case (~2.5 years). In addition, cases in medical literature report SCC developing in advanced HS, whereas in the presented case the condition is assessed as hurley I-II.…”
mentioning
confidence: 45%
“…Both lesions were removed surgically with security field of~1 cm (Figure 1b HS is a chronic, often impairing, skin disorder, manifested with forming of painful subdermal abscesses, sinus tracts and scarring in the areas with high apocrine glands count (axillae, gluteal area and anogenital area). 1 Complication of HS include: infection, scarring, limitations in movement and lymph drainage, but also malignisation. In 3.2% to 4.6% of the patients with HS a developing of squamous cell carcinoma (SCC) is seen.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been previously reported that patients with chronic HS have a 50% increased risk in the overall incidence of malignancy . In particular, the relative risk for squamous cell carcinoma is 4.6 with HS with most squamous cell carcinomas presenting on the perineal or buttock areas …”
Section: Discussionmentioning
confidence: 99%
“…A paper in 2016 by Jourabchi et al and in 2018 by Chapman et al described 80 and five cases, respectively, on SCC in patients with HS cases in the English literature. We found five additional cases of SCC arising from HS reported in the literature since the last updated review by Chapman et al (Table ). Among these five new cases, the mean history of HS prior to SCC diagnosis was 16 years, and the mean age at diagnosis was 51.2 years.…”
Section: Case Reportmentioning
confidence: 99%